2014
DOI: 10.1080/17445302.2014.944334
|View full text |Cite
|
Sign up to set email alerts
|

Coupled dynamics of deepwater structures – issues and challenges

Abstract: Offshore systems consisting of floaters linked to line structures such as risers and mooring lines are favoured for deepwater applications. The dynamic coupling analysis of a floater together with the line structures has been the subject of several studies in recent years. Powerful numerical tools have been developed implementing full-fledged time-domain approaches as well as more efficient frequency-domain approaches for the analysis of deepwater systems. The present article provides a brief overview of coupl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…The third member is the drag force that is related to the relative velocity of the segment and the seawater flow. The third member is used for the formulation of the damping within the motion equation [29,30]. Thus, the drag force is the damping in considerations of the mooring line dynamics.…”
Section: Loads On Mooring Linementioning
confidence: 99%
See 2 more Smart Citations
“…The third member is the drag force that is related to the relative velocity of the segment and the seawater flow. The third member is used for the formulation of the damping within the motion equation [29,30]. Thus, the drag force is the damping in considerations of the mooring line dynamics.…”
Section: Loads On Mooring Linementioning
confidence: 99%
“…Only one finite element was used for the segment with an assumption that the value of the axial deformation was constant over the element length. On the basis of the presented assumptions, we formulated the nodal displacements and the nodal tensions as per Equations ( 28) and (29), respectively:…”
Section: Straight Segmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Results showed that the lateral vibrations are negligible, and hence, the idea of using planar motion models seems to be a plausible approximation. Furthermore, a number of useful contributions to the analysis and design of marine risers or pipelines are available in the literature published in recent years (Ai et al, 2018;Lou et al, 2017;Park et al, 2015;Yuan et al, 2018;Khan and Ahmad, 2017;Li and Low, 2012;Guo et al, 2013;Gao et al, 2014;Gao et al, 2016;Xu et al, 2017;Bai et al, 2017;Zhang et al, 2015;Ye et al, 2014;Dong et al, 2013;Katifeoglou and Chatjigeorgiou, 2016;Park et al, 2018;Vendhan, 2014;Gu et al, 2017).…”
Section: Introductionmentioning
confidence: 99%